6-gingerol enhances ciprofloxacin efficacy by inhibiting NorA efflux pump in Staphylococcus aureus - Shashikanta Sau; Sarika Sharma; Gopal L. Khatik; Sandeep Sharma; Nitin Pal Kalia (The Microbe)
The drug efflux mechanism adopted by Staphylococcus aureus helps it in its survival under antibiotic pressure. The efflux pump NorA, a member of the MFS superfamily, effluxes out fluoroquinolones, biocides, quaternary ammonium compounds, and anti-infectives. Therefore, in a continuous effort to identify new scaffolds as NorA inhibitors, we in the present study screened 6-gingerol ((5S)-5-Hydroxy-1-(4-hydroxy-3-methoxyphenyl) decan-3-one) for its role as a NorA efflux pump inhibitor. 6-gingerol dramatically decreased the intracellular invasion and ciprofloxacin minimum inhibitory concentration (MIC) in NorA, overproducing S. aureus SA-1199B. Furthermore, 6-gingerol enhanced the killing efficacy and minimized the mutation frequency of ciprofloxacin. The accumulation of ethidium bromide, another substrate for NorA efflux pump, was significantly inhibited by 6-gingerol. A molecular docking on NorA protein suggested the potential role of 6-gingerol in inhibiting efflux pump via binding at the protein's active site. 6-gingerol showed an excellent binding affinity of −5.8 kcal/mol at NorA protein. Further, in an intracellular invasion assay performed using J774A. 1 macrophage cell lines, 6-gingerol significantly reduced the invasion of S. aureus SA-1199B (NorA overproducing) by 2 Log10. For the first time, the study delineated the role of 6-gingerol as an efflux pump inhibitor of S. aureus with a significant impact on intracellular invasion of the bacteria.